Does Implementation of Enhanced Recovery after Surgery (ERAS) Protocols in Colorectal Surgery Improve Patient Outcomes? - Ban, Kristen A.; Berian, Julia R.; Ko, Clifford Y. (Clinics in Colon and Rectal Surgery, 2019)
Enhanced Recovery after Surgery (ERAS) protocols are multimodal perioperative care pathways designed to accelerate recovery by minimizing the physiologic stress of a surgical procedure. Benefits of ERAS implementation in colorectal surgery include reduced length of stay and decreased complications without an increase in readmissions. Though there is evidence associating individual ERAS protocol elements (e.g., preoperative carbohydrate loading, judicious perioperative fluid administration, and early initiation of postoperative nutrition) with improved outcomes, ensuring high compliance with all elements of an ERAS protocol will maximize benefits to the patient. After ERAS implementation, data collection on protocol process measures can help providers target education and interventions to improve protocol compliance and patient outcomes.
Keywords: Enhanced Recovery after Surgery; fast-track surgery; outcomes